Epistemology of Hadith in Syafi'iyyah and It’s Effect in Istinbāṭ al-Ahkām - Imam Syafi’i; Subairi Subairi (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2022)
This study aims to examine the Hadith in the Syafi'iyah Ulama. Historically, the style of thought of the scholars has focused on two schools, namely: the mutakallim school pioneered by the Syafi'iyyah scholars and the Ahnāf school, known as the fuqahā', which the Hanafi scholars built. These two schools have different paradigms, including in the study of Hadith, especially when istinbāṭ al-Ahkām. There are three points obtained in this study; first, the Syafi'iyyah scholars divide the Hadith (from the aspect of quantity) into two, namely the mutawātir Hadith and the ahād Hadith. Second, the scholars agree that Mutawātir hadith can be used as a basis for a source of law. At the same time, the ahād Hadith and the mursal Hadith of the Syafi'iyyah scholars provide certain conditions in making the ahād Hadith and mursal Hadith sources of law. Third, from the aspect of qat'iy-ẓanniy and 'ām-takhs, in the view of the Syafi'iyyah scholars that the word 'āmm is Zanni, so the pronunciation of 'āmm, what is in the Qur'an can be interpreted with the Hadith ahād and Qiyas because they are both Zanni. Zanni argues that there is no obstacle to assessing the Zanni.